Scheduling and Monitoring of Water Supply Project at Jabalpur using Management Tool Primavera : A Review - Ramkrishan Soni; Pankaj Agrawal; Anudeep Nema (International Journal of Scientific Research in Civil Engineering, 2022)
Implementation of construction project needs a proper planning and scheduling is of vital importance for the project to be executed and run smoothly. A best schedule has to be prepared in such a way that meets the primary objectives of the total project. Those primary objectives are to create a quality project, completed on time, within budget, and in a safe work environment. IN this paper presenting review of literature related to monitoring controlling of a water supply project.
Keywords: Primavera; Gantt Chart; Time-Cost Comparison; Cpm Network; Tracking; Project Scheduling